Climate reporting quality following the recommendations of the task force on climate‐related financial disclosures: A Focus on the German capital market. (19th October 2022) - Braasch, Annabelle; Velte, Patrick
Abstract: This paper investigates the quality of climate reporting by German DAX30 companies based on legitimacy theory. The study refers to a content analysis of climate‐related corporate disclosures from 2018 to 2020, related to the recommendations of the Task Force on Climate‐related Financial Disclosures (TCFD). The results show that there is still considerable room for improvement among carbon‐sensitive as well as less carbon‐sensitive firms. In particular, the companies showed poor reporting rates in the corporate governance domain, indicating that they use climate reporting symbolically to present themselves in a favorable light and to gain legitimacy in society. Moreover, carbon‐sensitive companies were more likely to report strategically relevant information on climate issues. The results are most relevant for researchers, business practice and regulatory bodies.